Quality Development of Islamic Education in the Era of Society 5.0 : Oppurtunities and Challenges - Zamroni, Ahmad; Wakidi, Wakidi (Al-Mau'izhoh: Jurnal Pendidikan Agama Islam, 2023)
The purpose of this study is to look at the opportunities and challenges of developing the quality of Islamic education in the 5.0 era. This research is based on a library research approach, which involves collecting data and information from various sources in the literature. The results showed that Islamic education is faced with various challenges in developing quality in the 5.0 era. These challenges include providing educational facilities and improving the quality of human resources. The provision of educational facilities is directly related to limited access to technology and the quality of educational content. Meanwhile, improving the quality of human resources is directly related to the lack of technological skills, skills gaps, and lack of access to infrastructure. The opportunities that Islamic education has in developing the quality of education in the 5.0 era are the management of digital-based education management and the development of 21st century skills.